Analysis of a direct‐drive permanent magnet synchronous generator with novel toroidal winding. Issue 10 (7th May 2021) - Wei, Yanqi; Cheng, Zhiping; Si, Jikai; Jin, Fuli; Gao, Caixia; Gan, Chun
Abstract: Direct‐drive permanent magnet synchronous generators (DDPMSGs) are gaining more and more attention in the field of wind power because of the advantages of simple structure, high efficiency and high reliability. However, due to the extremely low rotational speed, large volume and heavy weight of DDPMSGs, it poses serious challenges for transportation and installation, which limits its application. Therefore, a DDPMSG with novel toroidal windings (NTW) is proposed to improve power density in this paper. Unlike regular windings, each coil of the NTWs is wound onto the stator yoke in the same direction. The special configuration enables the generator to have higher winding coefficient, so that the DDPMSG with NTWs (NTW‐DDPMSG) can achieve higher power density than traditional fractional slot concentrated windings (FCW). The proposed topology and operating principles are described in detail. To verify the merits of the proposed NTW‐DDPMSG, the electromagnetic parameters of two external rotor surface‐mounted DDPMSGs equipped with NTW and FCW respectively are designed. The characteristics of air‐gap magnetic field, no‐load electromotive force, output power, loss and efficiency are analysed on the conditions of different loads and speeds. Comparison results show that the proposed NTW‐DDPMSG has higher power density than FCW‐DDPMSG.